Means-tested transfer programs in the United States - Moffitt, Robert A. (National Bureau of Economic Research conference report., 2003)
Few United States government programs are as controversial as those designed to aid the poor. From tax credits to medical assistance, aid to needy families is surrounded by debate?on what benefits should be offered, what forms they should take, and how they should be administered. The past few decades, in fact, have seen this debate lead to broad transformations of aid programs themselves, with Aid to Families with Dependent Children replaced by Temporary Assistance to Needy Families, the Earned Income Tax Credit growing from a minor program to one of the most important for low-income families.